The open access for the education contents at Arab Open University according to student orientation modern technologies and the international attitudes اننفار انحر نهمحتىي انتعهيمي ببرامج انجامعت انعربيت انمفتىحت في ضىء اتجاهاث انطهبت وانتقنياث انحذيخت وانتىجهاث انعانميت - Al Musawii, Abdul Mutalib Sharaf Ali; Al-Hidabi, Dawood Abdulmalek Yahya; Tunku Ahmad, Tunku Badariah; Makkivi, Mohamed El Tahir Osman (Yayıncı OCERINT International Organization Center of Academic Research, 2019)
This quantitative study aims to identify the open access and feasibility of methods for the education contents at Arab Open University, under the level of trends of methods at Arab Open University. The study sample of consisted of 30 students from the fourth Master Program batch. The study utilized two measurements for data collection. The study found that the digital repositories, directory of open access and electronic books are considered the usable resources for student. While the open access is the lowest source that student use. Moreover, the study found the legal and technical obstacles are one of the most obstacles are one of the most that face open access at Arab Open University. However, technological and moral obstacles that face open access in Arab Open University. Finally, researcher suggested the number of recommendation and proposals that support open access at the university.